Implementasi PAI Melalui Kearifan Lokal sebagai Upaya Mengatasi Kecanduan Smart Phone Anak: Study Permainan Engklek di SDN Patahunan 01 Bogor - Rizki Ahmad Fauzan; Gunawan Ikhtiono; Indriya Indriya (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
In the current era of digitalization, both children, teenagers, and adults are addicted to smart phones. The impact of smartphone addiction is divided into two, one positive impact and the second negative impact. The biggest impact of smartphone addiction is experienced by school children in elementary, middle, and high schools. Where children become lazy, eyes are damaged, and attitudes towards teachers and parents are not polite. This study aims to find out "Implementation of PAI through Local Wisdom as an Effort to Overcome Children's Smart Phone Addiction (Study of Engklek Games at SDN PATAHUNAN 01 Bogor)". The method used in this research is descriptive qualitative research method, which is a research method that is shown to describe, analyze a phenomenon, as well as events in social activities, attitudes, beliefs, carefully in the form of written words from people and observed activities. . In conducting this research, the researcher used interview, observation (direct observation), and documentation to the object of research, namely students at SDN Patahunan 01 Bogor. The results of the research based on the formulation of the problem that have been carried out show that in every Traditional Game, both Engklek and others have Islamic Religious Education values, such as the value of honest character, value of tolerance character, value of discipline character, value of hard work character, value of creative character, value of friendly/communicative character, the value of peace-loving character and the value of cooperation. Keywords: Islamic Religious Education, Local Wisdom, Engklek, Smart Phone